2018
DOI: 10.1111/liv.13692
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and safety of transnasal compared to conventional endoscopy for detecting oesophageal varices in cirrhotic patients

Abstract: Unsedated transnasal endoscopy was safe and had an excellent accuracy and high interobserver agreement for detecting oesophageal varices and for identifying high-risk varices in cirrhotic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 30 publications
(73 reference statements)
0
14
0
Order By: Relevance
“…A further five studies which reported on diagnostic findings during ultra‐thin endoscopy were excluded due to the lack of comparison to a reference standard. Ten studies remained and were considered for data analysis (Figure ) . No further studies were identified through manually hand‐searching references of electronically retrieved articles (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A further five studies which reported on diagnostic findings during ultra‐thin endoscopy were excluded due to the lack of comparison to a reference standard. Ten studies remained and were considered for data analysis (Figure ) . No further studies were identified through manually hand‐searching references of electronically retrieved articles (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies included only people with suspected, but unknown presence of oesophageal varices (screening cohort) . In the remaining studies, people with an antecedent diagnosis of oesophageal varices were also enrolled (surveillance cohort) . Ultra‐thin endoscopes, with diameters ranging from 3.1 to 5.3 mm were used in all studies, but the make and model differed from study to study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations